Optimizing the Role of Posyandu in Suppressing Stunting Rates in Dringu Village, Dringu District, Probolinggo Regency - Risa Pramestia Hani; Adi Prasetyo; Eka Nuraini; Muhammad Mufid Ro'uf; Arimurti Kriswibowo (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2023)
Posyandu is a community-based health service facility that plays a role in achieving national development goals, namely, to reduce infant and toddler mortality. The problem of stunting is a condition of chronic malnutrition caused by a lack of nutritional intake over a long period of time. This causes disturbances in the child's development period. This activity aims to help optimize the role of Posyandu to reduce stunting rates in Dringu Village, Dringu District, Probolinggo Regency. The activities were carried out from March to June 2023 at the Dringu Village Posyandu. This service activity involves all cadres and the community of mothers of toddlers. This activity is carried out by analyzing and collecting information related to mothers' understanding of children's nutrition and stunting. The results of the study set priority issues on increasing the role of the Dringu Village Posyandu in suppressing stunting in children. Posyandu has an important role in handling stunting through nutrition monitoring and services as well as counseling and education. The Dringu Village Posyandu needs to be optimized so that Dringu Village becomes stunting free.